PTU-148 Does investigating chronic gastrointestinal symptoms following pelvic radiotherapy identify treatable diagnoses?. (28th May 2012) - Henson, C C; McLaughlin, J; Ang, Y; Babbs, C; Crampton, J; Kelly, M; Lal, S; Limdi, J; Whatley, G; Swindell, R; Makin, W; Davidson, S E
Abstract : Introduction: 17 000 patients are treated with radical pelvic radiotherapy per year in the UK. Although 50% develop significant chronic gastrointestinal (GI) symptoms, <20% are referred for gastroenterological evaluation. We aimed to determine the causes of GI symptoms in this patient group. Methods: 60 patients with GI symptoms ≥6 months after radical pelvic radiotherapy were identified from oncology clinics. Those requiring urgent investigation via the 2-week wait pathway were excluded. Baseline characteristics including demographic data, cancer treatment details and symptoms were collected. Patients were referred for gastroenterological evaluation using an algorithmic approach, which involves the identification of all GI symptoms and investigation for all potential causes for the individual symptoms. Details of investigations and diagnoses were collected. Results: 20 men and 36 women with primary gynaecological (31), urological (17) or lower GI (8) tumours were included, with a median age of 58.5 years (range 26.9–81.8). As part of their cancer treatment 15 patients also had brachytherapy, 28 had chemotherapy and 25 had surgery. Patients presented with multiple GI symptoms (median 8, range 4–16) including frequency (46), urgency (52), loose stool (50), faecal incontinence (40), flatulence (43), bloating/distension (38) and rectal bleeding (29). The median number of investigations per patient was 9 (range 1–17), including routine blood tests (47), coeliac screen (39), breath tests for small bowel bacterial overgrowth (21) and lactose intolerance (16), SeHCAT scans (27) and upper (27) and lower (38) GI endoscopy. Common diagnoses include radiation proctopathy (22) and bile acid mabsorption (12). Some diagnoses are unrelated to previous radiotherapy, for example, diverticulosis (9) and colonic polyps (8). No cause was found for symptoms in seven patients. 25 patients have 2 or more GI diagnoses. Conclusion: Gastroenterological evaluation identifies significant and potentially treatable diagnoses in patients who develop chronic GI symptoms following pelvic radiotherapy. Some findings are incidental and some are unrelated to previous cancer treatment. GI symptoms in these patients have historically been considered "untreatable". These data suggest that structured gastroenterological assessment has the potential to improve outcome by identifying these diagnoses and facilitating focussed treatment. Competing interests: None declared.